Utilization of a Learning Management System to Develop Critical Thinking Skills - Bugis, Fitri; Kusuma Wirasti, Murti; Nurani, Yuliani (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The concept of a Learning Management System (LMS) is a dynamic concept of critical thinking. This research aims to explain using LMS to develop critical thinking skills. This type of research is qualitative with a literature review. The data sources used secondary data from journals, books, and references. Data collection techniques were carried out with documentation, while data analysis was through content analysis. Learning Management System (LMS) can improve students’ critical thinking skills because it will familiarize students with problem-solving and/or learning from problems, as well as the educators in developing thinking skills. It was concluded that the Learning Management System (LMS) based discussion method could improve undergraduate students' critical thinking skills.